The association of metabolic syndrome score trajectory patterns with risk of all cancer types - Deng, Li; Liu, Tong; Liu, Chen‐An; Zhang, Qi; Song, Meng‐Meng; Lin, Shi‐Qi; Wang, Yi‐Ming; Zhang, Qing‐Song; Shi, Han‐Ping (Cancer, 2024)
Background Metabolic syndrome (MetS) elevates cancer risk. However, a single MetS assessment does not fully reveal the long‐term association with cancer. Inflammation, alongside MetS, could synergistically expedite both the onset and advancement of cancer. This study aims to investigate MetS score trajectories and cancer risk in a large, prospective cohort study. Methods The authors prospectively examined the relationship between MetS score trajectory patterns and new‐onset cancer in 44,115 participants. Latent mixture modeling was used to identify the MetS score trajectories. Cox proportional hazards regression models were used to evaluate the association between MetS score trajectory patterns and the risk of overall and site‐specific cancers. Results Four MetS score trajectory patterns were identified: low‐stable (n = 4657), moderate‐low (n = 18,018), moderate‐high (n = 18,288), and elevated‐increasing (n = 3152). Compared to participants with a low‐stable trajectory pattern, the elevated‐increasing trajectory pattern was associated with an elevated risk of overall (hazard ratio [HR], 1.27; 95% confidence interval [CI], 1.04–1.55), breast (HR, 2.11; 95% CI, 1.04–4.34), endometrial (HR, 3.33; 95% CI, 1.16–6.77), kidney (HR, 4.52; 95% CI, 1.17–10.48), colorectal (HR, 2.54; 95% CI, 1.27–5.09), and liver (HR, 1.61; 95% CI, 1.09–4.57) cancers. Among participants with chronic inflammation (C‐reactive protein levels ≥3 mg/L), the elevated‐increasing trajectory pattern was significantly associated with subsequent breast, endometrial, colorectal, and liver cancers. Conclusions Trajectories of MetS scores are associated with the occurrence of cancers, especially breast, endometrial, kidney, colorectal, and liver cancers, emphasizing the importance of long‐term monitoring and evaluation of MetS. Plain Language Summary The association between long‐term elevated metabolic syndrome (MetS) scores and a heightened risk of various cancers is a pivotal finding of our study. Our research further indicates that individuals with MetS, particularly when coupled with chronic inflammation, are at an increased risk of cancer. We propose that sustained monitoring and management of MetS could be beneficial in reducing cancer risk. Metabolic syndrome (MetS) score trajectories have been linked to an increased risk of several cancers, including breast, endometrial, kidney, colorectal, and liver cancers. This highlights the critical need for long‐term monitoring and evaluation of MetS.